Secession Debated : Georgia's Showdown in 1860. - Freehling, William W. (Oxford University Press, 2006)
The critical northern antebellum debate matched the rhetorical skills of Abraham Lincoln and Stephen A. Douglas in an historic argument over the future of slavery in a westward-expanding America. Two years later, an equally historic oratorical showdown between secessionists and Unionists inGeorgia generated as much popular interest south of the Mason-Dixon line, and perhaps had an even more profound immediate effect on the future of the United States. With Abraham Lincoln's "Black Republican" triumph in the presidential election of 1860 came ardent secessionist sentiment in the South